Computational Fluid Mechanics - Du, Peng; Ouahsine, Abdellatif; Hu, Haibao; Chen, Xiaopeng (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint collected the cutting-edge developments of CFD in the area of marine science and technology. CFD methods including novel numerical algorithms, advanced treatments of solving procedures, parallel acceleration techniques, and the utilization of CFD for fluid-structure interaction, wave modeling, ship dynamics, etc., are included. The audience of this reprint can be researchers and engineers in the area of marine science and technology.